The Source Base of Research of Scientific and Educational Heritage of Podillya Educator M.M.Darmansky - Slyuzko-Plakhtiy, Valentyna; Onyshchenko, Oleksandr (Pedagogical Discourse, 2013)
The source base on life and professional way of M.M.Darmansky as an outstanding educator and reformer of Podillya region is chosen and systematized according to the subject of the research. The analytical articles about his research and educational explorations and achievements in the field of pedagogical sciences are collected. The bibliography of publications on M.M.Darmansky has been compiled for the first time.